ADVANCING ENGLISH LANGUAGE LEARNING THROUGH PEDAGOGICAL TECHNOLOGIES - Djalilova Sabokhat Rixsibayevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
: The article discusses the transformative impact of technology on English language education. The article highlights the diverse array of pedagogical technologies available to educators and learners, including interactive platforms, digital resources, collaborative environments, assessment tools. By leveraging these technologies, educators can create dynamic and engaging learning experiences that cater to the diverse needs and preferences of learners.